2009
DOI: 10.4401/ag-3063
|View full text |Cite
|
Sign up to set email alerts
|

Cavola experiment site: geophysical investigations and deployment of a dense seismic array on a landslide

Abstract: Geophysical site investigations have been performed in association with deployment of a dense array of 95 3-component seismometers on the Cavola landslide in the Northern Apennines. The aim of the array is to study propagation of seismic waves in the heterogeneous medium through comparison of observation and modelling. The small-aperture array (130 m×56 m) operated continuously for three months in 2004. Cavola landslide consists of a clay body sliding over mudstone-shale basement, and has a record of historica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Therefore, the propagation of seismic waves into a slope could be potentially affected by the presence of a weakened shear band, which may modify the response at the ground surface even during weak earthquake motions. Furthermore, some studies have shown the characteristic directivity of the slope dynamic response to seismic shaking on the basis of geological, geophysical and in situ investigations (e.g., [51][52][53][54][55]). Moreover, a sloping surface can generate a parasitic vertical component of acceleration even for input motions characterised by horizontally polarised waves due to the reflection of the incoming waves from the inclined slope surface [19,56].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the propagation of seismic waves into a slope could be potentially affected by the presence of a weakened shear band, which may modify the response at the ground surface even during weak earthquake motions. Furthermore, some studies have shown the characteristic directivity of the slope dynamic response to seismic shaking on the basis of geological, geophysical and in situ investigations (e.g., [51][52][53][54][55]). Moreover, a sloping surface can generate a parasitic vertical component of acceleration even for input motions characterised by horizontally polarised waves due to the reflection of the incoming waves from the inclined slope surface [19,56].…”
Section: Introductionmentioning
confidence: 99%